The Issues of Sustainable Management of Innovative Industrial Risks During Sustainable Development of Entities - KADEEV, Z.K.; PONIKAROVA, A.S.; ZOTOV, M.A.; KADEEVA, E.N.; KANTYUKOV, R.R.; SHENKARENKO, S.V. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
This research considers the issues of the balanced management of innovative industrial risks as a mechanism for achieving sustainable development of entities. The place of this complex of management actions has been determined in the general strategic management system when introducing innovations in the context of disturbances and risks. The role of innovative industrial risks, as restrictions of innovative development, has been defined, and the main challenges of implementing balanced management principles when introducing innovations in the face of uncertainty have been analyzed. For research, the petrochemical complex of the Republic of Tatarstan has been selected, the features of its innovative development have been studied, and the main trends and approaches to managing innovative industrial risks at achieving sustainable development in present-day conditions have been identified.